Organization, inducible-expression and chromosome localization of the human HMG-I(Y) nonhistone protein gene. - Friedmann, M (1993)
Members of the HMG-I(Y) family of mammalian nonhistone proteins are of importance because they have been demonstrated to bind specifically to the minor groove of A.T-rich sequences both in vitro and in vivo and to function as gene transcriptional regulatory proteins in vivo. Here we report the cloning, sequencing, characterization and chromosomal localization of the human HMG-I(Y) gene. The gene has several potential promoter/enhancer regions, a number of different transcription start sites and numerous alternatively spliced exons making it one of the most complex nonhistone chromatin protein-encoding genes so far reported. The putative promoter/enhancer regions each contain a number of conserved nucleotide sequences for potential binding of inducible regulatory transcription factors. Consistent with the presence of these conserved sequences, we found that transcription of the HMG-I(Y) gene is inducible in human lymphoid cells by factors such as phorbol esters and calcium ionophores. Detailed sequence analysis confirms our earlier suggestion that alternative splicing of precursor mRNAs gives rise to the major HMG-I and HMG-Y isoform proteins found in human cells. Furthermore, the gene's exon-intron arrangement fully accounts for all of the previously cloned human HMG-I(Y) cDNAs (1,2). Also of considerable interest is the fact that each of the three different DNA-binding domain peptides present in an individual HMG-I(Y) protein is coded for by sequences present on separate exons thus potentially allowing for exon 'shuffling' of these functional domains during evolution. And, finally, we localized the gene to the short arm of chromosome 6 (6p) in a region that is known to be involved in rearrangements, translocations and other abnormalities correlated with a number of human cancers.